Strategi Pemetaan Kompetensi pada Seleksi Calon Penghulu di Lingkungan Kantor Wilayah Kementerian Agama Kalimantan Timur dan Kalimantan Utara: Strategy for Competence Mapping in Candidate Selection of Penghulu In the Regional Office of The Ministry of Religious Affairs East Kalimantan and North Kalimantan - Lia Rosliana; Mayahayati Kusumaningrum; Kemal Hidayah; Wildan Lutfi Arieyasmieta (Pusjar SKPP Lembaga Administrasi Negara, 2019)
Changes in the candidate selection process is a strategy in to improve human resources under the spirit of bureaucratic reform within the Ministry of Religious Affairs of Indonesia. The selection of position selection must pay attention to the competency mapping, as stipulated in Decree of Minister of Religion of the Republic of Indonesia Number 208 the Year 2017 concerning guidelines for adjustment/inpassing, competency test, and determination of functional needs of penghulu. This This research was a descriptive method with a qualitative approach, namely through a diagnosis from the desk research and review of the results of the competency test and core reports on the selection of prospective leaders in the Ministry of Religious Affairs of Republic Indonesia, East Kalimantan and North Kalimantan regional office. The results of the study showed that competency mapping strategies carried out in the selection of functional need of penghulu produce a profile officer that can be source information of candidate capability. This is conducted for the needs of functional development of penghulu in the future Competency mapping strategies need to be carried out continuously so that all the functional positions of penghulu can be optimally enhanced. Keywords: Selection, Strategy, Competence Mapping, Penghulu Abstrak Perubahan proses seleksi calon penghulu merupakan strategi dalam memperbaiki area perubahan sumber daya manusia sesuai dengan semangat reformasi birokrasi di lingkungan Kementerian Agama Republik Indonesia. Seleksi jabatan harus memperhatikan pemetaan kompetensi, sebagaimana yang diatur dalam Keputusan Menteri Agama Republik Indonesia Nomor 208 Tahun 2017 tentang Pedoman Penyesuaian/ Inpassing, Uji Kompetensi dan Penetapan Kebutuhan Jabatan Fungsional Penghulu. Penelitian ini bersifat deskriptif dengan pendekatan metode kualitatif, yaitu melalui analisis dari desk riset dan telaah hasil laporan uji kompetensi inti dan kompetensi manajerial pada seleksi calon penghulu di Kementerian Agama Republik Indonesia Kantor Wilayah Kalimantan Timur dan Kalimantan Utara. Hasil penelitian menunjukkan bahwa strategi pemetaan kompetensi yang dilakukan dalam seleksi jabatan fungsional penghulu memberikan hasil profil pegawai yang dapat dijadikan salah satu sumber informasi kemampuan peserta seleksi. Hal ini dilakukan untuk kepentingan pengembangan kepegawaian para fungsional penghulu dimasa yang akan datang. Strategi pemetaan kompetensi perlu terus dilakukan sehingga semua jabatan fungsional penghulu ini dapat ditingkatkan kompetensinya secara optimal. Kata Kunci: Seleksi, Strategi, Pemetaan Kompetensi, Penghulu